There are no safe areas for avoiding the perforating arteries along the proximal part of the femur: A word of caution. Issue 4 (13th May 2019) - Pretterklieber, Bettina; Pablik, Eleonore; Dorfmeister, Karl; Pretterklieber, Michael L.
Abstract : Knowledge about the variable course of the perforating arteries near the body of the femur is essential during surgical procedures (e.g., percutaneous cerclage wiring, plate osteosynthesis, Ilizarov technique). Our aims were to determine the number of perforating arteries, and to identify safe zones along the body of the femur within which perforating arteries are unlikely to pass toward the back of the thigh. The number of perforating arteries was determined in both legs of 100 formalin‐fixed anatomic specimens of both sexes. The level of passage of perforating arteries near the body of the femur was measured in reference to a line from the anterior superior iliac spine to the medial femoral condyle. In each leg, two to seven perforating arteries were present. In 64% of legs, at least one artery divided into two to four branches before entering the back of the thigh. Thus, the total number of branches passing near the body of the femur varied between two to nine. Perforating arteries passed to the back of the thigh at every level between 14.0 and 36.5 cm from the anterior superior iliac spine (16–39% of the leg length). Within this distance, no safe zones along the body of the femur could be identified. The present study shows the high variability regarding number and course of the perforating arteries. Surgeons can be faced with an artery at every level on the posteromedial aspect of the body of the femur between 14.0 and 36.5 cm distally to the anterior superior iliac spine. Clin. Anat. 33:507–515, 2020. © 2019 Wiley Periodicals, Inc.